Nonfimbrial Adhesin Mutants Reveal Divergent Escherichia coli O157:H7 Adherence Mechanisms on Human and Cattle Epithelial Cells. (29th January 2021) - Moreau, Matthew R.; Kudva, Indira T.; Katani, Robab; Cote, Rebecca; Li, Lingling; Arthur, Terrance M.; Kapur, Vivek
Abstract : Shiga toxin-producing, enterohemorrhagic Escherichia coli (EHEC) serotype O157:H7 is a major foodborne pathogen causing symptoms ranging from simple intestinal discomfort to bloody diarrhea and life-threatening hemolytic uremic syndrome in humans. Cattle can be asymptomatically colonized by O157:H7 predominantly at the rectoanal junction (RAJ). Colonization of the RAJ is highly associated with the shedding of O157:H7 in bovine feces. Supershedding (SS) is a phenomenon that has been reported in some cattle that shed more than 10 4 colony-forming units of O57:H7 per gram of feces, 100–1000 times more or greater than normal shedders. The unique bovine RAJ cell adherence model revealed that O157:H7 employs a LEE-independent mechanism of attachment to one of the RAJ cell types, the squamous epithelial (RSE) cells. Nine nonfimbrial adhesins were selected to determine their role in the characteristic hyperadherent phenotype of SS O157 on bovine RSE cells, in comparison with human HEp-2 cells. A number of single nucleotide polymorphisms (SNPs) were found amongst these nonfimbrial adhesins across a number of SS isolates. In human cells, deletion of yfaL reduced the adherence of both EDL933 and SS17. However, deletion of eae resulted in a significant loss of adherence in SS17 whereas deletion of wzzB and iha in EDL933 resulted in the same loss of adherence to HEp-2 cells. On RSE cells, none of these nonfimbrial deletion mutants were able to alter the adherence phenotype of SS17. In EDL933, deletion of cah resulted in mitigated adherence. Surprisingly, four nonfimbrial adhesin gene deletions were actually able to confer the hyperadherent phenotype on RSE cells. Overall, this study reveals that the contribution of nonfimbrial adhesins to the adherence mechanisms and functions of O157:H7 is both strain and host cell type dependent as well as indicates a possible role of these nonfimbrial adhesins in the SS phenotype exhibited on RSE cells.